THE IMPORTANCE OF BUILDING STUDENTS’ ENGAGEMENT DURING ONLINE LEARNING - Tri Pujiani (LPPM Universitas Harapan Bangsa, 2020)
ABSTRACT Students’ engagement can be defined as how much time, commitment, and effort is devoted to the learning process. Students’ engagement is an important element in learning because it is a factor that affects academic success. During the emergency online learning due to covid-19 pandemic, some problems emerged because of the lack of learning engagement. This descriptive study was aimed to find out the problems faced by the students and the lecturers during the online learning as well as the tips to build learning engagement. The study was carried out in July 2020 to the students and the lecturers of Harapan Bangsa University. The data obtained from questionnaire and semi structured interview showed that although the implementation of online learning has been good, there were still some problems to be solved. Moreover, learning engagement was absolutely required during the online learning. It is expected that the result of this study may be useful for lecturers in designing the effective online learning and also for the students in understanding their role during the learning process.